2021
DOI: 10.1016/j.compbiomed.2020.104171
|View full text |Cite
|
Sign up to set email alerts
|

Development of an absolute assignment predictor for triple-negative breast cancer subtyping using machine learning approaches

Abstract: Triple-negative breast cancer (TNBC) heterogeneity represents one of the main impediment to precision medicine for this disease. Recent concordant transcriptomics studies have shown that TNBC could be splitted into at least three subtypes with potential therapeutic implications.Although, a few studies have been done to predict TNBC subtype by means of transcriptomics data, subtyping was partially sensitive and limited by batch effect and dependence to a given dataset, which may penalize the switch to routine d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Moreover, we employed the GBM algorithm to identify the most predictive variables, and we used the SHAP method to interpret the outputs. Previous studies have discussed the use of different machine learning algorithms such as random forest, GBM, and the extreme boosting machine to find predictive variables in patients with BC [ 44 , 45 ]. However, there is no consensus about which algorithm should be used because the accuracy of each model mainly depends on the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we employed the GBM algorithm to identify the most predictive variables, and we used the SHAP method to interpret the outputs. Previous studies have discussed the use of different machine learning algorithms such as random forest, GBM, and the extreme boosting machine to find predictive variables in patients with BC [ 44 , 45 ]. However, there is no consensus about which algorithm should be used because the accuracy of each model mainly depends on the dataset.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Warnat-Herresthal et al found that ML-based transcriptomics can assist in the diagnosis of acute myeloid leukemia (63). Moreover, Ben Azzouz et al used an ML approach based on transcriptomics data to calculate triple-negative breast cancer subtypes, in order to overcome the barrier of heterogeneity in the treatment of the disease (64). Finally, some ML-based transcriptomics have also been used in the development of prognostic biomarkers for prostate cancer (65), the diagnosis of colorectal cancer (66), and the prediction of immune response (67).…”
Section: Ai Assists Pm For Tumors In Transcriptomicsmentioning
confidence: 99%
“…Machine learning is a new type of artificial intelligence, which has been widely used in medical data analysis and is a powerful tool for improving clinical strategies [14][15][16]. Some tree-based machine learning methods (such as survival tree [ST], random survival forest [RSF], and gradient boosting machine [GBM]) can account for interaction and effect modification between variables and have been applied in some prognosis studies [17][18][19][20][21][22][23][24][25][26][27]. In many studies, in which the categorical variable was the dependent variable, the prediction performance of machine learning is better than that of traditional models [6,14,28,29].…”
Section: Introductionmentioning
confidence: 99%